Wavelength and energy dependence on ablation dynamics under femtosecond laser pulses observed by time-resolved pump–probe microscopy. - Carrasco Garcia, Irene M.; Vadillo-Pérez, José Miguel; Laserna-Vázquez, José Javier (Elsevier, 2019)
Pump–probe femtosecond microscopy has been applied to reveal the time evolution of the ablation processes at sub-picosecond resolution with combined pulses of different photon energies. Experimental results revealed that differences in the photon energies of ablation pulses influenced the temporal response of the material. Significant differences in the excitation and melting of the material within 10 ps of irradiation were observed. The analysis of dynamic Newton's rings observed with the pump–probe technique confirmed and explained the faster expansion of ablated matter when using shorter irradiation wavelengths. The results also implied that optical properties of the material play a significant role.
https://openpolicyfinder.jisc.ac.uk/publication/15141
Keywords: Fotoquímica de láser; Láser